Interventions
VIII, 247 p.
Keywords: This collection brings together top scholars to discuss the significance of violence from a global perspective and the intersections between the global structures of violence and more localized and intimate forms of violence. Activists and academics consider questions such as; are there situations in which violence should be politically supported? Are non-violent or anti-war movements in the US able to effectively respond to violence? Do we need to rethink our understanding of both 'religion' and 'secularism' in light of the current world situation? Have new paradigms been developed in response to violence? The essays in this collection offer inclusive analysis of particular situations and creative alternatives to the omnipresence of violence.